Alterations in hepatic fatty acids reveal depletion of total polyunsaturated fatty acids following irinotecan plus 5-fluorouracil treatment in an animal model of colorectal cancer. (November 2021) - Monirujjaman, Md; Pant, Asha; Nelson, Randy; Bathe, Oliver; Jacobs, Rene; Mazurak, Vera C
Highlights: Hepatic DHA was depleted following chemotherapy treatment. Total TG was not elevated in the liver following one or two cycle of chemotherapy. Chemotherapy down regulates long chain PUFA converting genes including FADS2 and ELOVL2. Abstract: Fatty liver is a side effect of chemotherapy that limits the ability to treat colorectal cancer (CRC) patients in the most effective way. The aim of this study was to determine hepatic fatty acid composition and expression of genes involved in lipid metabolism at two time points following sequential chemotherapy treatment with Irinotecan (CPT-11)+5-fluorouracil (5-FU), agents commonly used to treat human colorectal cancer. Female Fischer 344 rats were provided a semi-purified AIN-76 basal diet with modified fat component. One cycle of chemotherapy consisted of CPT-11+5-FU and was initiated 2 weeks after tumor implantation (D0); a second cycle was given one week later. Two days after each cycle (Day 2 and Day 9), animals were euthanized, and livers collected. Triacylglycerol (TAG) and phospholipid (PL) fractions were isolated using thin layer chromatography and fatty acids (FAs) were quantified using gas chromatography. Expression of 44 lipid metabolism genes were analyzed by qPCR. Total liver TAG level was lowest after the second cycle D0 and D2 ( P  = 0.05) characterized by lower content of n-6 and n-3 polyunsaturated fatty acids (PUFAs). N-6 PUFAs significantly declined with subsequent treatments. Of 44 genes analyzed, 13 genes were altered with CPT-11+5-FU treatment. Expression of genes VLCAD and DGAT1, involved in fatty acid oxidation as well as DGAT1 in TAG synthesis, were significantly elevated after each cycle, whereas expression of genes ELOVL2 and FADS2, involved in fatty acid elongation and desaturation were significantly lower at D9 compared to D2 and D0 ( P  < 0.03). Hepatic total TAG PUFA was depleted, and genes involved in pathways of PUFA synthesis were down-regulated by chemotherapy treatment. This observation suggests impediments in lipid metabolism in the liver that could potentially impact peripheral availability of essential fatty acids.